Новые виды рода Rhaphium Mg. (Dolichopodidae, Diptera) фауны СССР - Негробов, О.П. (Вестник зоологии, 1977)
Four new for science species of the Rhaphium genus from Kazakhstan, Primoryc and the Kuril Islands are described. Differential diagnoses of the species are presented on
the basis of which the species are involved into the Becker table.